Method for extracting vaterite calcium carbonate and mixed chloride salt from waste incineration fly ash

Through water washing, gas-liquid phase reaction and photothermal interface evaporation, high-quality vaterite calcium carbonate and mixed chloride salt are extracted from waste incineration fly ash, solving the problems of product impurities, low added value and large energy consumption in the prior art, and achieving low carbon and efficient resource utilization.

CN118270819BActive Publication Date: 2025-03-04ZHEJIANG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410390594.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-02
Publication Date
2025-03-04
Estimated Expiration
2044-04-02

AI Technical Summary

Technical Problem

The prior art has problems such as many product impurities, low added value, and large energy consumption of the process route when extracting vaterite calcium carbonate and mixed chloride salt from waste incineration fly ash, making it difficult to achieve efficient resource utilization.

Method used

The pH value of the fly ash water washing solution is adjusted through water washing operation, combined with carbon dioxide bubbles and the use of L-aspartic acid, so as to achieve precipitation of calcium carbonate and separation of chloride salt. Then, the photothermal interface evaporator is used to perform photothermal interface evaporation, and the sodium-potassium chloride salt in the water washing liquid is recovered.

Benefits of technology

The extraction of high-quality vaterite calcium carbonate and mixed chloride salt is achieved, reducing the toxicity of heavy metal leaching, simple, safe, economical, environmentally friendly, and has no waste liquid production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118270819B_ABST
    Figure CN118270819B_ABST
Patent Text Reader

Abstract

The present invention relates to solid waste treatment technology, and aims to provide a method for extracting vaterite calcium carbonate and mixed chloride salt from waste incineration fly ash. It includes: after washing the waste incineration fly ash, adding NaOH solution and L-aspartic acid and mixing evenly; continuously introducing carbon dioxide gas under stirring, separating the mixed solution after the reaction is completed, and drying the white solid to obtain vaterite crystalline calcium carbonate; adding dilute hydrochloric acid to the filtrate to adjust the pH value, and ensuring that the salinity contained is below 15wt%; the filtrate is introduced as an evaporation mother liquor using an umbrella-shaped interface evaporator, and umbrella-shaped unidirectional water transmission and photothermal interface evaporation are realized under sunlight. This method performs directional regulation on the heavy metal leaching behavior affected by pH, and controls the migration direction of heavy metals; adding L-aspartic acid during wet carbonization can inhibit the growth of calcite crystals; by means of photothermal interface evaporation, no waste liquid is generated in the whole process; the process is simple, safe and economical, environmentally friendly and low-carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to solid waste treatment technology, in particular to a method for extracting vaterite calcium carbonate and mixed chloride salts from fly ash from garbage incineration, and belongs to the technical field of resource utilization of hazardous fly ash. Background Art

[0002] With the rapid development of economy, society and urbanization, the amount of garbage generated in urban life is huge. Due to the advantages of domestic waste incineration disposal technology such as fast volume reduction and heat energy utilization, its proportion in different garbage disposal schemes is constantly increasing, and the production of fly ash as the residue of domestic waste incineration is also constantly expanding. Since fly ash is enriched with most of the heavy metals, dioxins and other pollutants in the incineration flue gas, and has the characteristics of high calcium and high chlorine soluble salts, it has been included in the list of hazardous wastes (HW18). Improper disposal will cause environmental pollution. There is an urgent need for harmless disposal of fly ash, and its safe disposal has become one of the main challenges facing the domestic waste incineration industry.

[0003] The soluble salt content in fly ash is about 40-60wt%, which has high environmental migration risk and serious corrosion of operating equipment in various disposal processes. At the same time, the presence of chloride in fly ash soluble salt affects the performance of fly ash resource products, further limiting the resource utilization path. Fly ash soluble salt is mainly composed of sodium-potassium-calcium ternary system, and the traditional extraction steps include water washing-impurity removal-MVR evaporation crystallization. Due to the complex components of fly ash, a series of traditional evaporation fractionation crystallization technologies represented by mechanical vapor recompression (MVR) technology are used. The obtained sodium and potassium salts contain a certain concentration of heavy metals, organic carbon, ammonium salts, sulfates and other impurities, which affect the subsequent resource utilization. In addition, calcium ions form calcium carbonate during the impurity removal process, which is mixed with other impurities such as heavy metals and is difficult to utilize as resources. Therefore, MVR technology has the disadvantages of high energy consumption, difficult treatment of high-concentration waste salt in mother liquor, and low product added value.

[0004] The Chinese invention patent "A method for graded detoxification and resource utilization of pollutants in fly ash from the incineration of domestic waste" (CN202310893630.5) introduces a method for graded removal of soluble chloride salts, heavy metals and dioxins in fly ash, realizing the resource utilization of fly ash from the incineration of domestic waste. The purpose of this method is to acid wash the fly ash with waste sulfuric acid, without the need to consume hydrochloric acid, thereby reducing the cost of fly ash disposal and making it more suitable for industrial promotion. However, since calcium sulfate and magnesium sulfate are both slightly soluble, the degree of removal of calcium and magnesium ions in the water washing liquid is relatively low, and the sodium-potassium chloride salts obtained by subsequent evaporation fractionation and crystallization contain high impurities such as heavy metals; on the other hand, this method uses combined membrane filtration to remove excess calcium sulfate precipitates, but since the use of membrane technology has certain requirements on the salinity of the treated solution, the amount of water used in the treatment process is increased. The Chinese invention patent "Three-stage compressor series MVR evaporation treatment fly ash water washing liquid system and method" (CN116395772A) introduces a three-stage compressor series MVR evaporation treatment fly ash water washing liquid system, which uses three-stage steam compressors in series, which can effectively solve the impact of evaporation mother liquor concentration fluctuations on the evaporation system. However, due to the large increase in the boiling point of potassium chloride after enrichment and saturation, the effective temperature difference that MVR technology can provide in the actual process is only about 8°C. Even after improvement, the technology still requires a large amount of heat exchange area for the evaporation system, and key problems such as high operating energy consumption and large wastewater discharge still need to be solved.

[0005] From the above technical status and discussion, it can be seen that the current resource utilization technologies for soluble components of fly ash have many disadvantages such as high product impurities, low added value, and high energy consumption in the process route. Therefore, it is urgent to explore a low-carbon and efficient technology for recovering soluble sodium, potassium, calcium and chlorine components in fly ash. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for extracting vaterite calcium carbonate and mixed chloride salts from waste incineration fly ash.

[0007] In order to solve the technical problem, the solution of the present invention is:

[0008] A method for extracting vaterite calcium carbonate and mixed chloride salts from waste incineration fly ash is provided, comprising the following steps:

[0009] (1) washing the waste incineration fly ash with water, adjusting the pH value of the fly ash washing liquid to 9±0.5 with a hydrochloric acid solution; performing solid-liquid separation to obtain a fly ash washing liquid from which heavy metal ions are removed;

[0010] (2) Determination of Ca in fly ash washing liquid 2+ Concentration and quality of chloride salts; according to Ca 2+ :OH -The molar ratio is 1:1.5-2, and NaOH solution is added to the water washing solution; after mixing evenly, L-aspartic acid used as an inhibitor is added to the mixed solution and continued to mix evenly, and the amount of L-aspartic acid added is 5mM / L-80mM / L;

[0011] (3) continuously introducing carbon dioxide gas into the mixed solution obtained in step (2) by bubbling under continuous stirring; stopping the bubbling when the pH value of the mixed solution reaches 9 to 10, and performing solid-liquid separation on the mixed solution after the reaction is completed; and drying the separated white solid to obtain vaterite crystalline calcium carbonate;

[0012] (4) adding dilute hydrochloric acid to the filtrate obtained from the liquid-solid separation in step (3) to adjust the pH value to 7±0.5 to ensure that the salinity in the filtrate is less than 15 wt %;

[0013] (5) The filtrate obtained in step (4) is introduced as the evaporation mother liquor into an umbrella-shaped interface evaporator to achieve umbrella-shaped unidirectional water transmission and photothermal interface evaporation under sunlight:

[0014] The structure of the umbrella-shaped interface evaporator is as follows: the bottom is an open container for containing evaporation mother liquor, and filtrate is continuously added by a water inlet pipe to maintain an appropriate liquid level; the open part of the container is closed with insulation foam, and a long strip of hydrophilic carbon felt is vertically inserted into the central hole as a water transmission channel; one end of the water transmission channel is always below the liquid level, and the other end is fixed to the center of the interface evaporation disk made of super-hydrophilic carbon felt; the interface evaporation disk is horizontally seated on the insulation foam, and the interface evaporation disk and the water transmission channel together form an umbrella-shaped structure; the umbrella-shaped structure can extract the evaporation mother liquor to the surface interface of the interface evaporation disk for evaporation based on the capillary effect, and preferentially realize salt precipitation at the edge of the disk; the salt crystals produced during the salt precipitation process will gradually accumulate at the edge of the disk, and fall off by themselves due to gravity, and the fallen salt crystals are regularly collected.

[0015] As a preferred embodiment of the present invention, in the step (1), when washing the fly ash with water, the liquid-to-solid ratio is set to 3-5L:1kg; stirring is maintained for 90 minutes during the washing process, and the rotation speed is 1000 rpm; the concentration of the hydrochloric acid solution used to adjust the pH value is 1M; and filter press or centrifugation is used for solid-liquid separation.

[0016] As a preferred embodiment of the present invention, in step (2), the mass concentration of the NaOH solution is 10%; and the purity of the L-aspartic acid is 99%.

[0017] As a preferred embodiment of the present invention, in the step (3), the rate of introducing carbon dioxide gas is 200 mL / min, and the stirring rate is set to 500 rpm.

[0018] As a preferred embodiment of the present invention, in step (3), the drying treatment refers to placing the separated white solid in a forced air drying oven and drying it at a constant temperature of 100 to 105° C. for 12 hours.

[0019] As a preferred embodiment of the present invention, in step (4), the concentration of dilute hydrochloric acid is 1M.

[0020] As a preferred embodiment of the present invention, in step (5), the ratio of the diameter of the interface evaporation disk to the cross-sectional diameter of the water transmission channel is 8 to 12; the ratio of the length of the water transmission channel to the diameter of the interface evaporation disk is 1.8 to 2.5; and the ratio of the diameter of the interface evaporation disk to the diameter of the container is 1.1 to 1.3.

[0021] Description of the invention principle:

[0022] The invention combines the heavy metal leaching behavior of fly ash to control the heavy metal migration process in the water washing process, uses the calcium in the fly ash water washing liquid to capture carbon dioxide, and obtains high-quality vaterite calcium carbonate under the crystal form adjustment effect of the additive aspartic acid; at the same time, the effect of aspartic acid chelating calcium carbonate crystals to reduce solubility and force the calcium carbonate crystal form to deform, so that Ca in the photothermal evaporation process is reduced. 2+ The ions will not form scale at the light-absorbing load interface and reduce the evaporation rate.

[0023] The technical principle is described as follows:

[0024] (1) Fly ash dechlorination and pH adjustment:

[0025] Most of the soluble components of fly ash, such as sodium chloride, potassium chloride, calcium chloride and part of calcium hydroxide, are dissolved by water washing. The fly ash water washing liquid is acidified by using a hydrochloric acid solution of appropriate concentration. When the pH of the water washing liquid is adjusted to 9±0.5, the calcium hydroxide in the water washing liquid is neutralized and converted into calcium chloride, and most of the heavy metal ions are precipitated and migrated to the solid phase (i.e., detoxification). Through solid-liquid separation operation, a liquid enriched with sodium, potassium, calcium and chloride ions (mainly chloride salt) is obtained.

[0026] (2) Mechanism of gas-liquid phase reaction to form vaterite-type calcium carbonate:

[0027] The water washing liquid enriched with calcium ions can provide high concentration of calcium ions for the preparation of metastable vaterite calcium carbonate. The certain amount of NaOH added after acidification just provides the necessary alkaline environment for the formation of calcium carbonate, and the highly alkaline calcium-rich liquid is carbonated by carbonation reaction to generate calcium carbonate precipitation (i.e. decalcification) by bubbling with carbon dioxide. Since the conditions for the production of metastable vaterite are relatively harsh and it is easy to decompose and convert into calcite, the calcium carbonate crystal form in the carbonation precipitation crystallization process is adjusted by adding L-aspartic acid. L-aspartic acid carries a negatively charged carboxyl terminal group (α-COOH) and a polar side chain, which have a stronger ability to bind to the surface of calcite, thereby inhibiting its nucleation and / or crystal growth, while vaterite particles are relatively unaffected. Under high pH conditions (pH=10), the α-COOH groups and amino groups (α-NH2) of all amino acid molecules are completely deprotonated. Therefore, the functional groups of the side chains are effectively responsible for the overall charge of the molecules, and these molecules can interact with the surface of calcite calcium carbonate, thereby inhibiting the formation of calcite calcium carbonate in the entire reaction system.

[0028] (4) Umbrella-shaped one-way water transmission mechanism:

[0029] After the fly ash washing liquid has been detoxified and decalcified, the Ca 2+ It is basically completely converted into vaterite calcium carbonate, and the remaining water washing liquid is mainly composed of sodium potassium chloride salt. In the interface evaporation model of the umbrella-shaped unidirectional water transfer model, the evaporation rate of each point on the light-absorbing interface is basically the same. However, because the power of water transfer comes from the concentration gradient, the water supply rate is lower at the point farther from the inlet. As the evaporation process proceeds, the points at the edge of the evaporation interface will have a higher salinity and will be saturated earlier, resulting in preferential salt precipitation at the edge. Due to the existence of stable drainage channels in the area near the center, the salt crystals that appear during the dynamic evaporation process are also very easy to dissolve again and migrate to the edge. On this basis, by controlling the water transfer capacity and evaporation rate, the ion concentration on the upper surface of the evaporator (light-absorbing interface) can be controlled to be stable, thereby maintaining the cleanliness of the light-absorbing interface and the stable salt precipitation at the edge.

[0030] (5) Scale inhibition mechanism of evaporation interface:

[0031] The stability of solar interfacial evaporation is not only related to water scaling, evaporation rate, and mother liquor salinity; some special ions can also affect the stability of the evaporator during operation. In the one-way water transport theoretical model, Na + (1.334×10 - 5 cm 2 s -1 ) and K + (1.957×10 -5 cm 2 s-1 ) has a higher diffusion rate than Ca 2+ (0.792×10 -5 cm 2 s -1 ) and Mg 2+ (0.706×10 -5 cm 2 s -1 ), which means that the diffusion distance of brine containing magnesium and calcium ions is shorter than that of brine containing potassium and sodium ions. The ion diffusion rate determines the limit radius of stable salt precipitation of different chloride salts, and sodium and potassium chloride salts have similar "coffee ring" crystallization radius. In contrast, the salt ring radius of calcium and magnesium is too small, which will cause salt crystallization to occur on most areas of the surface of the evaporator of brine containing calcium and magnesium ions, which will lead to deterioration of evaporator performance and unstable operation.

[0032] The radius of the salt ring determines the possibility of contamination of the evaporator's light-absorbing interface. When the radius of the salt ring is smaller than the radius of the evaporator, the salt ring will appear on the light-absorbing interface of the evaporator, which will cause performance damage and contamination of the evaporator. The addition of L-aspartic acid will chelate calcium and magnesium ions to generate calcium aspartate and magnesium aspartate. These chelates are easily washed away, so that calcium and magnesium ions will not be deposited on the light-absorbing interface to form dirt.

[0033] The composition of fly ash washing liquid is complex. The content of calcium and magnesium ions (especially calcium ions) in fly ash washing liquid is not low. L-aspartic acid will react with Ca in the solution system. 2+ Mg 2+ The metal cations form coordination bonds to form soluble chelates (calcium aspartate and magnesium aspartate). This combination increases the Ca 2+ Solubility in aqueous solution and reduced Ca 2+ With CO3 2- 、SO4 2- In addition, the oxygen atoms in functional groups such as the carboxyl group and amino group in L-Asp will combine with the calcium atoms on the surface of the crystal in a chemical bond, occupying the active sites on the surface of the crystal, causing lattice distortion and hindering the normal growth of calcium scale crystals. Therefore, after adding the inhibitor L-aspartic acid, the scaling process of calcium and magnesium can be destroyed, thereby stabilizing the position of the crystal salt ring during the interface evaporation process.

[0034] Based on the above principle, the present invention couples gas-liquid carbonation with photothermal interface evaporation to achieve hierarchical resource utilization of soluble components contained in fly ash, co-produce high-quality calcium carbonate and mixed chloride salts, and regulate the gas-liquid carbonation reaction and the crystallization behavior of mixed chloride salts by using aspartic acid as an additive to obtain vaterite-type calcium carbonate and a stable crystalline mixed salt. First, the leaching of heavy metals during the fly ash washing process is reduced by adjusting the pH. When the pH is around 9, heavy metals such as Zn, Pb, Cu, and Ni in the fly ash are retained in the washed ash without migrating into the washing liquid. The gas-liquid reaction induced by CO2 makes the Ca in the fly ash washing liquid 2+ First, it is extracted in stages through the precipitation method; the decalcified fly ash water washing liquid is used as the evaporation mother liquor, and the sodium, potassium and chloride salts in the water washing liquid are recovered through photothermal interface evaporation. The addition of the inhibitor L-aspartic acid not only regulates the crystal form of calcium carbonate precipitation to vaterite, but also stabilizes the position of the crystal salt ring during the interface evaporation process, so that the photothermal interface evaporator can operate stably and achieve efficient and stable salt precipitation of the water washing liquid.

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] (1) This method can regulate the heavy metal leaching behavior affected by pH in the fly ash washing process in a targeted manner, thereby controlling the migration direction of the heavy metals so that they will not affect the subsequent resource utilization of the soluble components in the washing liquid.

[0037] (2) The method of the present invention adds L-aspartic acid during the wet carbonization process, which can inhibit the growth of calcite crystals, thereby stably preparing calcium carbonate crystals with a metastable vaterite structure.

[0038] (3) The present invention uses photothermal interface evaporation to recover sodium, potassium and chloride salts in fly ash washing liquid with low energy consumption using renewable energy, thereby achieving no waste liquid generation in the entire process; the salt ring position is stabilized by the scale inhibition effect of L-aspartic acid, thereby achieving continuous and stable operation of the device.

[0039] (4) The method of the present invention is simple in process, safe, economical, environmentally friendly and low-carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The present invention is a flow chart of the hierarchical treatment of extracting vaterite calcium carbonate and mixed chloride salts from waste incineration fly ash;

[0041] Figure 2 It is a schematic diagram of the photothermal interface evaporation device model in the present invention.

[0042] Figure 3 The XRD spectra of the calcite calcium carbonate prepared in the comparative example and the vaterite calcium carbonate prepared in the present invention;

[0043] Figure 4This is a SEM spectrum of common calcite calcium carbonate prepared by the method of the present invention without adding L-aspartic acid;

[0044] In the figure, (a) SEM image (10 μm) of calcite calcium carbonate prepared without adding L-aspartic acid; (b) SEM image (0.5 μm) of calcite calcium carbonate prepared without adding L-aspartic acid.

[0045] Figure 5 The SEM spectrum of vaterite calcium carbonate prepared by adding L-aspartic acid in the method of the present invention;

[0046] In the figure, (a) SEM image (50 μm) of vaterite calcium carbonate prepared after adding L-aspartic acid; (b) SEM image (5 μm) of vaterite calcium carbonate prepared after adding L-aspartic acid.

[0047] Figure 6 XRD diagrams of the mixed chloride salts prepared in the present invention and Comparative Example 1;

[0048] Figure 7 It is the record graph of evaporation rate of fly ash water washing liquid without / with L-aspartic acid added;

[0049] In the figure, (a) no L-aspartic acid was added; (b) L-aspartic acid was added. DETAILED DESCRIPTION

[0050] The present invention is further described below by way of embodiments in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0051] like Figure 1 As shown, the method for extracting vaterite calcium carbonate and mixed chloride salt from waste incineration fly ash in the present invention comprises the following steps:

[0052] (1) washing the waste incineration fly ash with water, adjusting the pH value of the fly ash washing liquid to 9±0.5 with a hydrochloric acid solution; performing solid-liquid separation to obtain a fly ash washing liquid from which heavy metal ions are removed;

[0053] The washing liquid contains a large amount of sodium chloride, potassium chloride and calcium chloride. After washing, a large amount of calcium hydroxide, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide and other substances remain in the fly ash, and almost all heavy metals are retained in the solid phase without leaching and migrating into the liquid phase.

[0054] As an example, when washing the fly ash, the liquid-to-solid ratio is set to (3-5):1 (L / kg); stirring is maintained for 90 minutes during the washing process, and the rotation speed is 1000 rpm; the concentration of the hydrochloric acid solution used to adjust the pH value is 1M; filter pressing or centrifugation is used for solid-liquid separation.

[0055] (2) Determination of Ca in fly ash washing liquid 2+Concentration and quality of chloride salts; according to Ca 2+ :OH - The molar ratio is 1: (1.5-2), and NaOH solution is added to the water washing solution; after mixing evenly, L-aspartic acid used as an inhibitor is added to the mixed solution and continued to mix evenly, and the amount of L-aspartic acid added is 5mM / L-80mM / L;

[0056] As an example, the mass concentration of the NaOH solution is 10%; the purity of L-aspartic acid is 99%.

[0057] (3) continuously introducing carbon dioxide gas into the mixed solution obtained in step (2) by bubbling under continuous stirring; stopping the bubbling when the pH value of the mixed solution reaches 9 to 10, and performing solid-liquid separation on the mixed solution after the reaction is completed; and drying the separated white solid to obtain vaterite crystalline calcium carbonate;

[0058] As an example, the rate of introducing carbon dioxide gas is 200 mL / min, and the stirring rate is set to 500 rpm. Drying treatment can be carried out by placing the separated white solid in a forced air drying oven and drying it at a constant temperature of 100-105° C. for 12 hours.

[0059] (4) adding dilute hydrochloric acid to the filtrate obtained from the liquid-solid separation in step (3) to adjust the pH value to 7±0.5 to ensure that the salinity in the filtrate is below 15 wt %; the ions in the filtrate are mainly sodium ions, potassium ions and chloride ions.

[0060] As an example, the concentration of dilute hydrochloric acid is 1M.

[0061] (5) The filtrate obtained in step (4) is introduced as the evaporation mother liquor into an umbrella-shaped interface evaporator to achieve umbrella-shaped unidirectional water transmission and photothermal interface evaporation under sunlight:

[0062] The structure of the umbrella-shaped interface evaporator is as follows Figure 2 As shown: the bottom is an open container for holding the evaporation mother liquor, and the filtrate is continuously added by the water inlet pipe to maintain the appropriate liquid level; the open part of the container is closed with insulating foam, and a long strip of hydrophilic carbon felt is vertically inserted into its central hole as a water transmission channel; one end of the water transmission channel is always located below the liquid surface, and the other end is fixed to the center of the interface evaporation disk made of super hydrophilic carbon felt; the interface evaporation disk is horizontally seated on the insulating foam, and the interface evaporation disk and the water transmission channel together form an umbrella-shaped structure; the umbrella-shaped structure can extract the evaporation mother liquor to the surface interface of the interface evaporation disk for evaporation based on the capillary effect, and preferentially realize salt precipitation at the edge of the disk; the salt crystals produced during the salt precipitation process will gradually accumulate at the edge of the disk, and fall off by themselves due to gravity, and the fallen salt crystals are collected regularly.

[0063] As an example, the ratio of the diameter of the interface evaporation disk to the cross-sectional diameter of the water transmission channel is 8 to 12; the ratio of the length of the water transmission channel to the diameter of the interface evaporation disk is 1.8 to 2.5; the ratio of the diameter of the interface evaporation disk to the diameter of the container is 1.1 to 1.3;

[0064] Using the umbrella-shaped interface evaporator, the mother liquid was evaporated under a sunlight intensity of 96 mW / cm 2 The evaporation rate under the light intensity of ) can reach 1.2 kg m -2 h -1 Even in natural environment, the evaporation rate can reach 0.25-0.35 kg m -2 h -1 For the evaporation mother liquid with a salinity of 10.8 wt%, the theoretical evaporation limit of the umbrella-type photothermal interface evaporation device is 1.4 kg m - 2 h -1 , the salt production rate reached 0.136kg m -2 h -1 After decalcification, the evaporation mother liquor can be completely removed through the interface evaporation process. After calculating the mass of the recovered salt crystals, the salt recovery efficiency of the umbrella-shaped interface evaporator reaches 99%.

[0065] Example 1

[0066] In this embodiment, the waste incineration fly ash is taken from a waste incineration plant in Zhejiang Province. The heavy metal leaching concentration of the fly ash washing liquid under the HJ / T 557-2010 standard is shown in Table 1.

[0067] The processing process in this embodiment specifically includes the following steps:

[0068] (1) Wash the waste incineration fly ash with water, and set the washing liquid-solid ratio to 3:1 (L / kg). Add an appropriate amount of 1M industrial hydrochloric acid (about 15% of the total volume of the fly ash washing mixture) during the washing process, stir with magnetic force for 90 minutes at a speed of 1200 rpm; monitor the pH value of the mixture in real time and control the pH at 9±0.5. Vacuum filter the washed mixture for solid-liquid separation to obtain acidified washed fly ash, and separate the solid-liquid mixture after acid leaching. The liquid part is the acid leaching liquid and enters step (2). The solid part is collected and placed in an oven for drying at room temperature and pressure.

[0069] (2) Determination of Ca in the washing liquid 2+ Concentration, according to Ca 2+ :OH -NaOH with a mass concentration of 10% was added to the water washing liquid at a molar ratio of 1:1.5, and the mixture was mixed evenly to obtain a mixed solution; L-aspartic acid with a concentration of 5 mM / L was added to the mixed solution, and the mixture was mixed evenly by magnetic stirring for 30 minutes at a speed of 800 rpm.

[0070] (3) Continuously introduce carbon dioxide gas into the mixed solution obtained in step (2) by bubbling, the carbon dioxide introduction rate is 200 mL / min, stirring is continued during the introduction process, and the stirring rate is set to 500 rpm. The pH in the solution is monitored in real time. When the pH reaches 9 to 10, the bubbling is stopped, and the solid-liquid separation is performed on the solution after the reaction. The separated white solid is placed in a blast drying oven, the temperature is set to 102 degrees Celsius, and the constant temperature is dried for 12 hours;

[0071] (4) Add 1 M dilute hydrochloric acid to the filtrate after liquid-solid separation in step (3) to adjust the pH to 7±0.5, measure the conductivity of the solution to determine the approximate range of the salt content of the solution, and ensure that the salinity is below 15 wt %.

[0072] (5) An umbrella-shaped interface evaporator is prepared using super-hydrophilic carbon felt, and the ratio of the diameter of the interface evaporation disk to the cross-sectional diameter of the water transmission channel is 8. The ratio of the diameter of the interface evaporation disk to the diameter of the evaporation container is 1.1. The ratio of the length of the water transmission channel to the diameter of the interface evaporation disk is 1.8. Select foam with good thermal insulation performance and cut it to a size that fits tightly against the inner wall of the container. Punch holes in the center of the interface evaporation disk and the insulation foam, with the size of the hole slightly larger than the cross-sectional size of the water transmission channel. Place the interface evaporation disk on the insulation foam, connect it through the hole through a long strip of water transmission channel, and place it inside the evaporation container so that the foam is tightly stuck to the inner wall of the container, and adjust the position to ensure that the surface level of the interface evaporation disk is consistent.

[0073] (6) The filtrate after adjusting the pH in step (4) was injected into the evaporation container, and the simulated light source was activated to ensure that the light intensity was within the range of one sun intensity (96 mW / cm 2 ), and the device is operated in an intermittent operation mode of 16h lighting environment + 8h natural environment.

[0074] (7) Salt crystals will continue to increase in weight as they precipitate at the edge. After every 72 hours of operation, the salt crystals that naturally fall off the edge of the interface evaporation disk are combined and recovered.

[0075] The evaporation mother salinity used this time is approximately 10.8wt%.

[0076] The average evaporation efficiency of the evaporator for 24 hours is 1.26 kg m -2 h -1 The salt precipitation rate is 0.136 kg m -2 h-1 .

[0077] The salt crystals recovered by crystallization were crushed, and then the heavy metal leaching test was carried out using the HJ / T 557-2010 standard. The leaching results are shown in Table 1:

[0078] Table 1 Heavy metal leaching concentrations of fly ash water wash and product of Example 1 (mg / L)

[0079]

[0080] ND: Not Detected

[0081] like Figure 4 As shown, the sample prepared in this example is mainly composed of calcium carbonate, and its surface morphology presents a dense structure.

[0082] Example 2

[0083] In this embodiment, the waste incineration fly ash is selected the same as that in Embodiment 1.

[0084] The operation process of this embodiment is consistent with that of embodiment 1, and some parameters in each step are adjusted as follows:

[0085] (1) Wash the waste incineration fly ash with water, and set the washing liquid-solid ratio to 4:1 (L / kg). Add an appropriate amount of 1M industrial hydrochloric acid (about 12% of the total volume of the fly ash washing mixture) during the washing process, stir with magnetic force for 90 minutes at a speed of 1200 rpm; monitor the pH value of the mixture in real time and control the pH at 9±0.5. Vacuum filter the washed mixture for solid-liquid separation to obtain acidified washed fly ash, and separate the solid-liquid mixture after acid leaching. The liquid part is the acid leaching liquid and enters step (2). The solid part is collected and placed in an oven for drying at room temperature and pressure.

[0086] (2) Determination of Ca in the washing liquid 2+ Concentration, according to Ca 2+ :OH - NaOH with a mass concentration of 10% was added to the water washing liquid at a molar ratio of 1:1.75, and the mixture was mixed evenly to obtain a mixed solution; L-aspartic acid with a concentration of 40 mM / L was added to the mixed solution, and the mixture was mixed evenly by magnetic stirring for 30 minutes at a speed of 800 rpm.

[0087] (3) Continuously introduce carbon dioxide gas into the mixed solution obtained in step (2) by bubbling, the carbon dioxide introduction rate is 200 mL / min, stirring is continued during the introduction process, and the stirring rate is set to 500 rpm. The pH in the solution is monitored in real time. When the pH reaches 9 to 10, the bubbling is stopped, and the solid-liquid separation is performed on the solution after the reaction. The separated white solid is placed in a blast drying oven, the temperature is set to 105 degrees Celsius, and the constant temperature is dried for 12 hours;

[0088] (4) Add 1 M dilute hydrochloric acid to the filtrate after liquid-solid separation in step (3) to adjust the pH to 7±0.5, measure the conductivity of the solution to determine the approximate range of the salt content of the solution, and ensure that the salinity is below 15 wt %.

[0089] (5) An umbrella-shaped interface evaporator is prepared using super-hydrophilic carbon felt, and the ratio of the diameter of the interface evaporation disk to the cross-sectional diameter of the water transmission channel is 10. The ratio of the diameter of the interface evaporation disk to the diameter of the evaporation container is 1.2. The ratio of the length of the water transmission channel to the diameter of the interface evaporation disk is 2.2. Select foam with good thermal insulation performance and cut it to a size that fits closely to the inner wall of the container. Punch holes in the center of the interface evaporation disk and the insulation foam, with the size of the hole slightly larger than the cross-sectional size of the water transmission channel. Place the interface evaporation disk on the insulation foam, connect it through the hole through a long strip of water transmission channel, and place it inside the evaporation container so that the foam is tightly stuck to the inner wall of the container, and adjust the position to ensure that the surface level of the interface evaporation disk is consistent.

[0090] (6) The filtrate after adjusting the pH in step (4) was injected into the evaporation container, and the simulated light source was activated to ensure that the light intensity was within the range of one sun intensity (96 mW / cm 2 ), and the device is operated in an intermittent operation mode of 16h lighting environment + 8h natural environment.

[0091] (7) Salt crystals will continue to increase in weight as they precipitate at the edge. After every 72 hours of operation, the salt crystals that naturally fall off the edge of the interface evaporation disk are combined and recovered.

[0092] The evaporation mother salinity used this time is approximately 8.2wt%.

[0093] The average evaporation efficiency of the evaporator for 24 hours is 1.18 kg m -2 h -1 The salt precipitation rate is 0.944 kg m -2 h -1 .

[0094] The salt crystals recovered by crystallization were crushed, and then the heavy metal leaching test was carried out using the HJ / T 557-2010 standard. The leaching results are shown in Table 2:

[0095] Table 2 Heavy metal leaching concentrations of fly ash water wash and product of Example 2 (mg / L)

[0096]

[0097] ND: Not Detected

[0098] Example 3

[0099] In this embodiment, the waste incineration fly ash is selected the same as that in Embodiment 1.

[0100] The operation process of this embodiment is consistent with that of embodiment 1, and some parameters in each step are adjusted as follows:

[0101] (1) Wash the waste incineration fly ash with water, and set the washing liquid-solid ratio to 5:1 (L / kg). Add an appropriate amount of 1M industrial hydrochloric acid (about 10% of the total volume of the fly ash washing mixture) during the washing process, stir with magnetic force for 90 minutes at a speed of 1200 rpm; monitor the pH value of the mixture in real time and control the pH at 9±0.5. Vacuum filter the washed mixture for solid-liquid separation to obtain acidified washed fly ash, and separate the solid-liquid mixture after acid leaching. The liquid part is the acid leaching liquid and enters step (2). The solid part is collected and placed in an oven for drying at room temperature and pressure.

[0102] (2) Determination of Ca in the washing liquid 2+ Concentration, according to Ca 2+ :OH - NaOH with a mass concentration of 10% was added to the water washing liquid in a molar ratio of 1:2, and the mixture was mixed evenly to obtain a mixed solution; L-aspartic acid with a concentration of 80 mM / L was added to the mixed solution, and the mixture was mixed evenly by magnetic stirring for 30 minutes at a speed of 800 rpm.

[0103] (3) Continuously introduce carbon dioxide gas into the mixed solution obtained in step (2) by bubbling, the carbon dioxide introduction rate is 200 mL / min, stirring is continued during the introduction process, and the stirring rate is set to 500 rpm. The pH in the solution is monitored in real time. When the pH reaches 9 to 10, the bubbling is stopped, and the solid-liquid separation is performed on the solution after the reaction. The separated white solid is placed in a blast drying oven, the temperature is set to 100 degrees Celsius, and the constant temperature is dried for 12 hours;

[0104] (4) Add 1 M dilute hydrochloric acid to the filtrate after liquid-solid separation in step (3) to adjust the pH to 7±0.5, measure the conductivity of the solution to determine the approximate range of the salt content of the solution, and ensure that the salinity is below 15 wt %.

[0105] (5) An umbrella-shaped interface evaporator is prepared using super-hydrophilic carbon felt, and the ratio of the diameter of the interface evaporation disk to the cross-sectional diameter of the water transmission channel is 12. The ratio of the diameter of the interface evaporation disk to the diameter of the evaporation container is 1.3. The ratio of the length of the water transmission channel to the diameter of the interface evaporation disk is 2.5. Select foam with good thermal insulation performance and cut it to a size that fits tightly against the inner wall of the container. Punch holes in the center of the interface evaporation disk and the insulation foam, with the size of the hole slightly larger than the cross-sectional size of the water transmission channel. Place the interface evaporation disk on the insulation foam, connect it through the hole through a long strip of water transmission channel, and place it inside the evaporation container so that the foam is tightly stuck to the inner wall of the container, and adjust the position to ensure that the surface level of the interface evaporation disk is consistent.

[0106] (6) The filtrate after adjusting the pH in step (4) was injected into the evaporation container, and the simulated light source was activated to ensure that the light intensity was within the range of one sun intensity (96 mW / cm 2 ), and the device is operated in an intermittent operation mode of 16h lighting environment + 8h natural environment.

[0107] (7) Salt crystals will continue to increase in weight as they precipitate at the edge. After every 72 hours of operation, the salt crystals that naturally fall off the edge of the interface evaporation disk are combined and recovered.

[0108] The evaporation mother salinity used this time is approximately 7.0wt%.

[0109] The average evaporation efficiency of the evaporator for 24 hours is 1.18 kg m -2 h -1 The salt precipitation rate is 0.083 kg m -2 h -1 .

[0110] The prepared samples were crushed, and then the heavy metal leaching test was carried out using the HJ / T 557-2010 standard. The leaching results are shown in Table 3:

[0111] Table 3 Heavy metal leaching concentrations of fly ash water wash and product of Example 3 (mg / L)

[0112]

[0113] ND: Not Detected

[0114] It can be seen from the analysis and test results of each embodiment that the process proposed by the present invention can grade the soluble components in the fly ash to obtain high-purity vaterite and mixed chloride salts. In addition, the heavy metal leaching toxicity of the calcium carbonate and mixed chloride salts prepared by the present invention is significantly reduced, which is far lower than the requirements for heavy metal leaching for resource utilization specified in the "Technical Specifications for Pollution Control of Fly Ash from Incineration of Domestic Waste" (HJ 1134-2020).

[0115] Comparative Example 1

[0116] In this comparative example, the waste incineration fly ash was taken from a waste incineration plant in Zhejiang Province. The heavy metal leaching concentration of the fly ash washing liquid under the HJ / T 557-2010 standard is shown in Table 1.

[0117] The processing process in this comparative example specifically includes the following steps:

[0118] (1) Wash the waste incineration fly ash with water, and set the washing liquid-solid ratio to 3:1 (L / kg). Add an appropriate amount of 1M industrial hydrochloric acid (about 15% of the total volume of the fly ash washing mixture) during the washing process, stir with magnetic force for 90 minutes at a speed of 1200 rpm; monitor the pH value of the mixture in real time and control the pH at 9±0.5. Vacuum filter the washed mixture for solid-liquid separation to obtain acidified washed fly ash, and separate the solid-liquid mixture after acid leaching. The liquid part is the acid leaching liquid and enters step (2). The solid part is collected and placed in an oven for drying at room temperature and pressure.

[0119] (2) Determination of Ca in the washing liquid 2+ Concentration, according to Ca 2+ :OH - NaOH with a mass concentration of 10% was added to the water washing solution in a molar ratio of 1:1.5, and the mixture was evenly mixed to obtain a mixed solution; the mixture was magnetically stirred for 30 minutes at a rotation speed of 800 rpm.

[0120] (3) continuously introducing carbon dioxide gas into the mixed solution obtained in step (2) by bubbling, the carbon dioxide introduction rate is 200 mL / min, stirring is continued during the introduction process, and the pH in the solution is monitored in real time. When the pH reaches 9 to 10, the bubbling is stopped, and the solution after the reaction is subjected to solid-liquid separation. The separated white solid is placed in a forced air drying oven set at a temperature of 100 to 105 degrees Celsius and dried at a constant temperature for 12 hours;

[0121] (4) Add 1 M dilute hydrochloric acid to the filtrate after liquid-solid separation in step (3) to adjust the pH to 7±0.5, measure the conductivity of the solution to determine the approximate range of the salt content of the solution, and ensure that the salinity is below 15 wt %.

[0122] (5) The size of the photothermal interface evaporator is determined by the salt content determined in step (4), and an umbrella-shaped interface evaporator is prepared using super-hydrophilic carbon felt, wherein the ratio of the diameter of the interface evaporation disk to the cross-sectional diameter of the water transmission channel is 8. The ratio of the diameter of the interface evaporation disk to the diameter of the evaporation container is 1.1. The ratio of the length of the water transmission channel to the diameter of the interface evaporation disk is 1.8. Select foam with good thermal insulation performance and cut it to a size that fits closely to the inner wall of the container. Punch holes in the center of the interface evaporation disk and the insulating foam, with the hole size slightly larger than the cross-sectional size of the water transmission channel. Place the interface evaporation disk on the insulating foam, connect it through the hole through a long strip of water transmission channel, and place it inside the evaporation container so that the foam is tightly stuck to the inner wall of the container, and adjust the position to ensure that the surface level of the interface evaporation disk is consistent.

[0123] (6) The filtrate after pH adjustment in step (4) is injected into the evaporation container, and the simulated light source is activated to ensure that the light intensity is about one sun, and the device is operated in an intermittent operation mode of 16 hours of light environment + 8 hours of natural environment.

[0124] (7) Salt crystals will continue to increase in weight as they precipitate at the edge. After every 72 hours of operation, the salt crystals that naturally fall off the edge of the interface evaporation disk are combined and recovered.

[0125] The evaporation mother salinity used in Comparative Example 1 was 10.9 wt%. The average evaporation efficiency of the evaporator over 24 hours was 1.25 kg m -2 h -1 The salt precipitation rate is 0.138 kg m -2 h -1 .

[0126] The salt crystals recovered from the crystallization are crushed, and samples are taken for observation to obtain SEM spectra such as Figure 4 It can be seen that the sample prepared in Comparative Example 1 is mainly composed of calcium carbonate, and the surface morphology presents a dense structure.

[0127] Subsequently, the heavy metal leaching test was carried out using the HJ / T 557-2010 standard. The leaching results are shown in Table 1:

[0128] Table 1 Heavy metal leaching concentrations of fly ash water wash and comparative example 1 products (mg / L)

[0129]

[0130] ND: Not Detected

[0131] Figure 3The lower middle curve is the XRD spectrum of the calcite calcium carbonate obtained in Comparative Example 1. Compared with the XRD spectrum of the vaterite calcium carbonate obtained in Example 1 of the present invention, which is the upper curve in the figure, it can be seen that: compared with Comparative Example 1, the number of absorption peaks of the calcium carbonate obtained in Example 1 increases a lot, and the peaks (004), (110), (112) and the like are all absorption peaks of vaterite calcium carbonate, which indicates that after adding L-aspartic acid, most of the calcium carbonate obtained by decalcification of the water wash is converted from calcite to vaterite.

[0132] Figure 4 The SEM spectra of ordinary calcite calcium carbonate prepared without adding L-aspartic acid in Comparative Example 1, the left and right figures are at different magnifications. It can be seen from the figure that the calcium carbonate precipitate obtained in Comparative Example 1 is mostly distributed in flakes and spindles, and is sharp in microscopic form; under a high-power electron microscope, it can be observed that the original carbonized rod-shaped calcium carbonate is composed of square crystals stacked and grown layer by layer, so it can be judged that the crystal form of this part of calcium carbonate is calcite.

[0133] Figure 5 For adding the SEM spectrogram of the prepared vaterite calcium carbonate of L-aspartic acid in the embodiment of the present invention 1, the left and right figures are respectively different magnifications.As can be seen from the figure, the calcium carbonate obtained by embodiment 1 can be observed under the scanning electron microscope, and the overall ups and downs are gentle in the calcium carbonate after the regulation, and there is a huge amount of obvious spherical or ellipsoidal vaterite, which illustrates that the crystallization process of calcium carbonate has played a selection to the vaterite growth by the regulation means.

[0134] Figure 6 XRD diagram of the mixed chloride salt prepared by the present invention and comparative example 1; it can be seen from the figure that under the action of aspartic acid, the crystal plane intensities of (111), (200) and (220) in the mixed chloride salt are reduced, while the intensity of the (110) peak is increased. This shows that aspartic acid changes the precipitation behavior and crystal form of the mixed chloride salt during the crystallization process. Compared with the (110) crystal plane, the ions of the (220) crystal plane are arranged more closely and the crystal plane density is higher. This arrangement leads to smaller gaps on the crystal plane. Therefore, the pores of the mixed chloride salt precipitated by evaporation with the addition of aspartic acid are larger, which is more suitable for stable operation of long-term evaporation.

[0135] Figure 7 The evaporation rate of the fly ash water washing liquid without / with L-aspartic acid added is recorded. It can be seen from the figure that after adding L-aspartic acid in Example 1, the evaporation performance of the evaporator can be kept stable for a long time during the interface evaporation process; while in Comparative Example 1, L-aspartic acid is not added, and the evaporation performance of the evaporator deteriorates rapidly after 10 hours, and long-term stable operation cannot be achieved.

[0136] In summary, the method for extracting vaterite calcium carbonate and mixed chloride salt from waste incineration fly ash provided by the present invention has the effect of efficiently capturing, fixing and permanently sealing carbon dioxide, and has the effect of efficiently solidifying and stabilizing heavy metals in waste incineration fly ash. At the same time, the prepared high-purity vaterite can be used for high-value utilization, such as hot pressing dissolution recrystallization treatment to obtain ceramic parts with high compressive strength, thereby realizing high-value utilization of fly ash; the mixed chloride salt obtained by solar interface evaporation can be used for molten salt heat storage power generation and hygroscopic power generation. Therefore, the invention is a waste incineration fly ash resource utilization technology with a very practical engineering application prospect, low cost, low carbon and environmental protection.

[0137] Obviously, those skilled in the art may make various subsequent applications, supplements, modifications and variations to the present invention without departing from the spirit and scope of the present invention. If various applications, supplements, modifications and variations based on the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include such applications, supplements, modifications and variations.

Claims

1. A method for extracting vaterite calcium carbonate and mixed chloride salts from waste incineration fly ash, characterized in that: The following steps are involved: (1) Washing the waste incineration fly ash with water, setting the liquid-solid ratio to 3-5 L:1 kg, and adjusting the pH value of the fly ash washing liquid to 9±0.5 with hydrochloric acid solution; performing solid-liquid separation to obtain the fly ash washing liquid with heavy metal ions removed; (2) Determination of Ca in fly ash washing liquid 2+ Concentration and quality of chloride salts; according to Ca 2+ :OH - The molar ratio is 1:1.5-2, and NaOH solution is added to the water washing solution; after mixing evenly, L-aspartic acid used as an inhibitor is added to the mixed solution and continued to mix evenly, and the amount of L-aspartic acid added is 5mM / L-80mM / L; (3) continuously introducing carbon dioxide gas into the mixed solution obtained in step (2) by bubbling under continuous stirring; stopping the bubbling when the pH value of the mixed solution reaches 9 to 10, and performing solid-liquid separation on the mixed solution after the reaction is completed; and drying the separated white solid to obtain vaterite crystalline calcium carbonate; (4) adding dilute hydrochloric acid to the filtrate obtained by liquid-solid separation in step (3) to adjust the pH value to 7±0.5 to ensure that the salinity of the filtrate is less than 15 wt%; (5) The filtrate obtained in step (4) is introduced as the evaporation mother liquor into an umbrella-shaped interface evaporator to achieve umbrella-shaped unidirectional water transmission and photothermal interface evaporation under sunlight: The structure of the umbrella-shaped interface evaporator is as follows: the bottom is an open container for containing evaporation mother liquor, and filtrate is continuously added by a water inlet pipe to maintain an appropriate liquid level; the open part of the container is closed with insulation foam, and a long strip of hydrophilic carbon felt is vertically inserted into the central hole as a water transmission channel; one end of the water transmission channel is always below the liquid level, and the other end is fixed to the center of the interface evaporation disk made of super-hydrophilic carbon felt; the interface evaporation disk is horizontally seated on the insulation foam, and the interface evaporation disk and the water transmission channel together form an umbrella-shaped structure; the umbrella-shaped structure can extract the evaporation mother liquor to the surface interface of the interface evaporation disk for evaporation based on the capillary effect, and preferentially realize salt precipitation at the edge of the disk; the salt crystals produced during the salt precipitation process will gradually accumulate at the edge of the disk, and fall off by themselves due to gravity, and the fallen salt crystals are regularly collected.

2. The method according to claim 1, characterized in that: In the step (1), stirring is maintained for 90 minutes during the water washing process at a rotation speed of 1200 rpm; the concentration of the hydrochloric acid solution used to adjust the pH value is 1 M; and filter pressing or centrifugation is used for solid-liquid separation.

3. The method according to claim 1, characterized in that: In the step (2), the mass concentration of the NaOH solution is 10%; the purity of L-aspartic acid is 99%.

4. The method according to claim 1, characterized in that: In the step (3), the rate of introducing carbon dioxide gas is 200 mL / min, and the stirring rate is set to 500 rpm.

5. The method according to claim 1, characterized in that: In the step (3), the drying treatment refers to placing the separated white solid in a forced air drying oven and drying it at a constant temperature of 100-105° C. for 12 hours.

6. The method according to claim 1, characterized in that: In the step (4), the concentration of dilute hydrochloric acid is 1 M.

7. The method according to claim 1, characterized in that: In the step (5), the ratio of the diameter of the interface evaporation disk to the cross-sectional diameter of the water transmission channel is 8-12; the ratio of the length of the water transmission channel to the diameter of the interface evaporation disk is 1.8-2.5; and the ratio of the diameter of the interface evaporation disk to the diameter of the container is 1.1-1.3.

Citation Information

Patent Citations

  • Three-stage compressor series connection MVR evaporation treatment fly ash water washing liquid system and method

    CN116395772A

  • Classified detoxification resource utilization method for household garbage incineration fly ash pollutants

    CN116871303A

  • Harmless resourceful treatment method for waste incineration fly ash

    CN111408602A

  • Method and device for continuous salt extraction from brine

    CN111818979A